Tropical cyclone genesis over the western North Pacific simulated by Coupled Model Intercomparison Project Phase 6 models - Gao, Cong; Zhou, Lei (Acta oceanologica Sinica, 2022)
Threatening millions of people and causing billions of dollars in losses, tropical cyclones (TCs) are among the most severe natural hazards in the world, especially over the western North Pacific. However, the response of TCs to a warming or changing climate has been the subject of considerable research, often with conflicting results. In this study, the abilities of Coupled Model Intercomparison Project (CMIP) Phase 6 (CMIP6) models to simulate TC genesis are assessed through historical simulations. The results indicate that a systematic humidity bias persists in most CMIP6 models from corresponding CMIP Phase 5 models, which leads to an overestimation of climatological TC genesis. However, the annual cycle of TC genesis is well captured by CMIP6 models. The abilities of 25 models to simulate the geographical patterns of TC genesis vary significantly. In addition, seven models are identified as well simulated models, but seven models are identified as poorly simulated ones. A comparison of the environmental variables for TC genesis in the well-simulated group and the poorly simulated group identifies moisture in the mid-troposphere as a key factor in the realistic simulation of El Niño-Southern Oscillation (ENSO) impacts on TC genesis. In contrast with the observations, the poorly simulated group does not reproduce the suppressing effect of negative moisture anomalies on TC genesis in the northwestern region (20°–30°N, 120°–145°E) during El Niño years. Given the interaction between TC and ENSO, these results provide a guidance for future TC projections under climate change by CMIP6 models.